Determinants of Sales Force Performance in Banking Sector: A Case of Malaysia - Kosim, Zunarni; Ahmad, Nor Hayati; Choo, Tan Sek (Information Management and Business Review, 2016)
Globalisation, deregulation, technology, competition and new customers’ needs influence the banks to adopt marketing approach in promoting their product and services to generate income. In this aspect, personal selling which focuses on selling skills of banking employees becomes a very important banking function. This study intends to investigate the relationship between the determinants namely teamwork, learning, leadership, communication and, high performance culture and Key Performance Indicators (KPI). Inspite of the importance of KPI in measuring performance of salesforce, there is a lack of published empirical findings to explain the influence of these predictors on KPI achievement in banking sector.This study reported that the model explains 0.21 percent of the variance in KPI achievement. In which teamwork and high performance culture are found to be positive and significantly related. This new finding appears to imply that bank should cultivate and promote teamwork and high performance culture to ensure KPI highly achievable and enhance banks profitability.